Beyond The Historiography: Film Dokumenter Sejarah Sebagai Alternatif Historiografi di Indonesia - Aan Ratmanto (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2018)
The Department of History, Faculty of Cultural Sciences, the University of Gadjah Mada in 2015 made a milestone in the development of historiography in Indonesia. They made a bold move to produce a scholar with a documentary film work instead of a thesis. In the future, it is not impossible that this step will soon be followed by other universities in Indonesia. This paper was written in response to these developments. In this digital era-and in the midst of still low interest in reading in Indonesia-emerged the discourse to seek new media for historiography in Indonesia. The film, especially documentary films are seen as new media that match the characteristics of history because of they both present real-life reality. Moreover, Indonesia with the diversity of tribes and culture and history, of course, save a variety of themes that will not run out to be appointed a documentary. Based on that, this paper will discuss the types, forms, and format of the documentary that is suitable and possible to be produced by history students as a substitute for thesis-considering the cost of film production tends to be higher than thesis research. Thus, the film of a documentary a college student, especially a history produces the quality of research and aestheticsKata